Network Sharing: Cooperating, Co-opting and Competing - Kalyan Dasgupta; Mark Williams (International Telecommunications Society (ITS), 2017)
Network sharing arrangements are common between mobile operators in Europe. There is also increasing interest in “co-investment” between fixed networks. Such arrangements have generally been cleared by anti-trust authorities. However, with the industry continually evolving and new types of sharing arrangements being proposed, it is important to review the competition implications of such deals.
Keywords: 330